THE ROLE OF WORK MOTIVATION IN IMPROVING EMPLOYEE PERFORMANCE IN ISLAMIC EDUCATIONAL INSTITUTIONS - Syuhud, Syuhud (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
As a learning agents, Islamic Religious Education Teachers (GPAI) have a central role in building the quality of PAI learning. One of the factors that influence the quality of PAI learning is the selection to learnthe  right learning approach by GPAI in designing and managinto learnng. Therefore, in the context of learning reform that should be carried out by PAI teachers is how to change the pattern of PAI learning activities which are dominated by the application of conventional (teacher-oriented) learning approaches to student-oriented learning approaches. One of them is a problem-solving strategy. The purpose of this research is an effort to cover GPAI skills in exploring students' abilities to think creatively, critically and rationally through problem-solving learning models and strategies. This study uses a qualitative approach to the type of library research. Sources of research data come from books, journals and scientific articles. All data obtained were analyzed with a hermeneutic scalpel. The results of this study indicate that problem-solving learning strategies can stimulate students to think creatively, critically and rationally. The motivation for work is based on employees' increased performance in Islamic educational institutions. Educational institutions are various formal institutions with different individual characters and motivations. Motivation Work appears in the behaviour of everyone inside an activity or work, and motivation is a person's mental state that drives to do something giving action-guiding force to achievement need. Motivation can raise encouragement or Work Spirit for every individual. Push or Spirit of work is strongly influenced by factors situation, workmate, policy, reward, type of work, and moderate challenges someone faces. This objective study reveals another aspect of the base motivation of employees to increase performance to get results and work maximum according to the stated target. This article uses the qualitative method, data collection using the form of interviews and observations, and then For analyze data using interactive analysis. The data obtained conclude that motivation for the work of teachers and employees in institutions of Islamic education is not only financially oriented, but other factors can underlie the base motivation of teachers and employees, that as intention devotion For practising knowledge with reward as a form of worship to Allah SWT. Intention and sincerity is the main asset for teachers and employees in institutions of Islamic education, so performance they Keep going to experience positive changes and developments for progress and quality education in institutions of Islamic teaching.